Brazilian experience with atopy patch tests for Dermatophagoides pteronyssinus, Dermatophagoides farinae and Blomia tropicalis - Souza Lima, Ingrid Pimentel Cunha Magalhães de (World Allergy Organ J, 2018)
BACKGROUND: The aim of this study was to evaluate the positivity rates of atopy patch tests for Dermatophagoides pteronyssinus, Dermatophagoides farinae and Blomia tropicalis in patients with respiratory diseases such as asthma and allergic rhinitis with or without atopic dermatitis. METHODS: The patients’ clinical histories were collected, and the patients were subjected to skin prick and patch tests with the three different house dust mites on the same day. The patch tests were examined 48 hours later, and then patients were divided into two groups: I- patients with respiratory diseases, such as asthma and/or rhinitis, and atopic dermatitis and II-patients with only respiratory diseases. A total of 74 patients ranging in age from 2 to 60 years were included in this study; 16 patients were included in group I and 58 were included in group II. This study was approved by the human ethics committee of the Faculty of Medical Science and Health SUPREMA (number 2.007.135), and written informed consent was collected from each patient or their parents prior to enrollment. RESULTS: In the skin prick tests, the most prevalent mite that evoked a reaction was Dermatophagoides pteronyssinus, followed by Dermatophagoides farinae and Blomia tropicalis. Regarding the atopy patch tests, the mite that most frequently induced a positive reaction was Dermatophagoides farinae (78.4%), followed by Dermatophagoides pteronyssinus (77%) and Blomia tropicalis (52.7%). A comparison of the skin prick and atopy patch tests revealed that 53 patients (71.6%) were positive on both tests, and 30 (56.6%) patients were positivite for the same mite. We found six patients (8%) who had a positive clinical history of allergy and only exhibited positivity on the atopy patch test. DISCUSSION: Most studies have been performed with atopic dermatitis patients, but in this study, most of the patients had respiratory conditions. Blomia tropicalis is a mite that is prevalent in tropical areas, such as Brazil, and only two publications include these three mites, wich are present in Brazil. The APT may produce positive results in concordance with the SPT resuts, but may also be the only positive test ( 8%) as we observed in our study. These results suggest that the mite atopy patch test is relevant and should be considered as an additional test for patients with clinical histories of allergic respiratory disease who have negative prick test results. CONCLUSION: The APT should be considered as an additional test when the SPT and specific serum IgE tests are negative in patients with clinical histories of allergies.